ON “THE FIRST DOCUMENTARY EVIDENCE FOR QARA QORUM FROM THE YEAR 635/1237-8.” - Mark A. Whaley (Acta Mongolica, 2011)
Since the publication of my Square Script paper (Whaley 2003-2004), a number of coins with the inscription I worked on have surfaced in the intervening years which I was unable to include, the most significant being a coin discovered in 2004 during excavations at Kara Korum by the Mongolian Academy of Sciences and the Universitat Bonn, but not publicized until 2005.' Since the matter is still pertinent, I think to revisit my conclusions and add further details would be an interesting topic.